Acute Effect of Repeated Sprint Exercise With Blood Flow Restriction During Rest Periods on Muscle Oxygenation - Kojima, Chihiro; Yamaguchi, Keiichi; Ito, Hiroto; Kasai, Nobukazu; Girard, Olivier; Goto, Kazushige (Frontiers in Physiology, 2021)
Purpose This study aimed to examine the effect of applying BFR during rest periods of repeated cycling sprints on muscle oxygenation. Methods Seven active males performed 5 × 10-s maximal pedaling efforts with 40-s passive rest, with or without BFR application during rest period. BFR was applied for 30 s between sprints (between 5 and 35 s into rest) through a pneumatic pressure cuff inflated at 140 mmHg. Vastus lateralis muscle oxygenation was monitored using near-infrared spectroscopy. In addition, blood lactate concentration and heart rate were also evaluated. Results The BFR trial showed significantly lower oxyhemoglobin (oxy-Hb) and tissue saturation (StO2) levels than the CON trial (P < 0.05). However, power output and blood lactate concentration did not significantly differ between the two trials (P > 0.05). Conclusion Applying BFR during rest periods of repeated cycling sprints decreased muscle oxygenation of active musculature, without interfering with power output during sprints.